Pemanfaatan Media Sosial Sebagai Sarana Memperluas Startegi Pemasaran Pada UMKM Terasi Bawang di Kec. Kaliwedi, Kabupaten Cirebon - Suherman, Mela Oktora; Faizal, Muhammad (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2024)
This study aims to analyze the use of social media as a means of expanding marketing strategies by MSMEs producing onion paste in Kaliwedi District, Cirebon Regency. The study used a descriptive qualitative approach with a purposive sampling technique, involving ten MSME actors who actively use social media such as Instagram, TikTok, WhatsApp, and Facebook. Data were collected through semi-structured interviews, observations, and documentation, and analyzed thematically and supported by descriptive statistics. The results of the study indicate that consistent use of social media, especially TikTok and Instagram, can significantly increase customer interaction and product sales. MSMEs that upload content more than four times per week experience an increase in sales of up to 33%. The SWOT analysis shows that MSMEs are in a strategic position for growth, although they still face obstacles in digital literacy and maximum utilization of platform features. This study recommends digital training, collaboration with local influencers, and integration of social media with marketplaces as further strategies. These findings are relevant for the development of locally-based digital marketing strategies, as well as supporting the economic empowerment of rural communities.